2013
DOI: 10.4103/0971-6866.116126
|View full text |Cite
|
Sign up to set email alerts
|

Association between PRO12ALA polymorphism of the PPAR-γ2 gene and type 2 diabetes mellitus in Iranian patients

Abstract: BACKGROUND:Peroxisome proliferator-activated receptor (PPARs) have been identified as ligand-activated transcription factors that belong to the nuclear receptor superfamily. It has been shown that an association exists between Proline 12 alanine (Pro12Ala) polymorphism of PPAR-GAMMA2 (PPAR-γ2) gene and increased risk of type 2 diabetes mellitus (T2DM) in different populations. Therefore, the present study was designed to investigate the association between Pro12Ala polymorphism of PPAR-γ2 gene and T2DM in an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…TCF7L2 variant rs7903146 a C-to-T (genomic position: 114748339) substitution in intron 3 and PPAR-γ2 Pro12Ala have been most extensively studied in all major ethnic groups and were found to be more consistently associated with the risk of developing T2DM in most of populations, such as Asians, Africans, and Caucasians [ 12 , 13 ]. These associations were also observed in most of the Arab populations of MENA region like Tunisians, Lebanese, [ 14 18 ], Iranian [ 19 , 20 ], and North Africans [ 21 ]. Although these polymorphisms were established as risk factor for T2DM in most of the populations studied so far, however, some of the studied polymorphisms seem not to be a major contributor to T2DM susceptibility in the Saudi and Emirati Arab populations [ 22 24 ].…”
Section: Introductionmentioning
confidence: 69%
“…TCF7L2 variant rs7903146 a C-to-T (genomic position: 114748339) substitution in intron 3 and PPAR-γ2 Pro12Ala have been most extensively studied in all major ethnic groups and were found to be more consistently associated with the risk of developing T2DM in most of populations, such as Asians, Africans, and Caucasians [ 12 , 13 ]. These associations were also observed in most of the Arab populations of MENA region like Tunisians, Lebanese, [ 14 18 ], Iranian [ 19 , 20 ], and North Africans [ 21 ]. Although these polymorphisms were established as risk factor for T2DM in most of the populations studied so far, however, some of the studied polymorphisms seem not to be a major contributor to T2DM susceptibility in the Saudi and Emirati Arab populations [ 22 24 ].…”
Section: Introductionmentioning
confidence: 69%
“…Association of Pro12Ala polymorphism of PPAR γ with T2DM was investigated in three studies [ 41 , 69 , 75 ]. Negative significant association of Ala/Ala genotype with T2DM was observed in two studies ( P = 0.003) [ 41 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Association of Pro12Ala polymorphism of PPAR γ with T2DM was investigated in three studies [ 41 , 69 , 75 ]. Negative significant association of Ala/Ala genotype with T2DM was observed in two studies ( P = 0.003) [ 41 , 75 ]. Ala/Pro carriers were shown to be positively associated in one study [ 41 ] and negatively associated in another study [ 75 ] with T2DM ( P < 0.001 and P = 0.003, resp.).…”
Section: Resultsmentioning
confidence: 99%
“…59,193 Motavallian et al compared the allele distributions of Pro12Ala polymorphism between healthy individuals and those with diabetes. 188 They found a higher frequency of the Ala allele12 in healthy individuals than in patients with diabetes. Another study found a protective role of high Ala frequency against T2DM as it was associated with increased insulin sensitivity, while low frequency of the Ala12 allele was associated with decreased insulin sensitivity (insulin resistance), which may lead to diabetes.…”
Section: Pparγ2mentioning
confidence: 96%
“…187 The PPARγ2 gene plays roles in glucose homeostasis, lipid metabolism, obesity, insulin sensitivity, T2DM, and various adipocytespecific genes. 59,[188][189][190] Based on several case-control and family-based studies, estimated that Pro12 allele (ie, the major allele) of PPARγ was associated with a 1.25-fold elevated risk of T2DM. 191 Further, the study of Chan et al showed that the Pro12Ala polymorphism was associated with T2DM risk in the multiethnic Women's Health Initiative (WHI) Observational Study at a nominal significance level (Pro12 allele is the risk-increasing allele, p=0.01, additive model).…”
Section: Pparγ2mentioning
confidence: 99%